(untitled) (Papeles, 2025)
Introduction: University social linkage has emerged as a strategic tool to strengthen the tax culture in vulnerable territories. Its role as an agent of change allows promoting social transformation from an educational and participatory approach, especially in contexts where popular businesses and informal economies predominate. This research seeks to make visible the impact of these interventions, highlighting the need to promote tax equity and inclusion. Methodology: The study was developed under a mixed approach, with a descriptive and cross-sectional design. Surveys, interviews and direct observations were applied to entrepreneurs of popular businesses. This methodological combination made it possible to collect qualitative and quantitative information that delves into the accounting and tax practices of the economic actors studied. Results and discussion: The findings revealed a low level of knowledge about tax obligations, myths about taxation and ignorance of existing incentives in Ecuadorian regulations. Despite the fear of sanctions, the entrepreneurs were willing to receive training. This openness allowed the execution of training workshops that sensitized participants on the importance of tax compliance as a basis for local development. Conclusions: The university social linkage not only generated relevant data, but also boosted formative processes that promote formalization and economic empowerment. Making these impacts visible reinforces their value as a strategy for inclusion, equity and sustainability in territories historically excluded from the tax system.